2014
DOI: 10.1371/journal.pone.0099042
|View full text |Cite|
|
Sign up to set email alerts
|

Small Intestinal Intraepithelial TCRγδ+ T Lymphocytes Are Present in the Premature Intestine but Selectively Reduced in Surgical Necrotizing Enterocolitis

Abstract: BackgroundGastrointestinal barrier immaturity predisposes preterm infants to necrotizing enterocolitis (NEC). Intraepithelial lymphocytes (IEL) bearing the unconventional T cell receptor (TCR) γδ (γδ IEL) maintain intestinal integrity and prevent bacterial translocation in part through production of interleukin (IL) 17.ObjectiveWe sought to study the development of γδ IEL in the ileum of human infants and examine their role in NEC pathogenesis. We defined the ontogeny of γδ IEL proportions in murine and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…58 TCR gd IEL have been shown to be recruited early to the premature gut (by 24 week gestation in humans and 1 week postnatally in mice), possibly to promote barrier function while the epithelial barrier is immature. 59 Mucin expression can be detected as early as 6.5 weeks gestation, but expressional patterns continue to undergo maturation throughout gestation. 60 While development of barrier function occurs in utero, there is ongoing postnatal maturation and multiple factors can induce postnatal intestinal barrier maturation including growth factors, hormones, nutrients and microbes.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…58 TCR gd IEL have been shown to be recruited early to the premature gut (by 24 week gestation in humans and 1 week postnatally in mice), possibly to promote barrier function while the epithelial barrier is immature. 59 Mucin expression can be detected as early as 6.5 weeks gestation, but expressional patterns continue to undergo maturation throughout gestation. 60 While development of barrier function occurs in utero, there is ongoing postnatal maturation and multiple factors can induce postnatal intestinal barrier maturation including growth factors, hormones, nutrients and microbes.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…al, reported that human NEC samples demonstrate markedly reduced occludin gene expression (compared to age-matched controls). 59 These studies emphasize the disparities among studies with regard to which TJ components are altered. It is also difficult to fully assess these data as in most studies, it is unclear if the authors chose to report only those components where changes occurred.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…The neonate is highly dependent on the innate immune system in the first 6 months, prior to the full maturation of the adaptive immune system, which is also compensated for by increased activity of gamma-delta T cells (76), including in premature infants (77). As the adaptive immune system develops, gamma-delta T cells continue to be significant modulators of gut responses, including the activity levels of Th1 and Th17 cells, with gamma-delta T cells being subject to negative feedback effects by regulatory T cells (78).…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%
“…Notably, some of these important factors are linked to TLR4 signalling. Furthermore, T lymphocytes have been shown to participate in the adaptation of the premature intestinal mucosa to bacterial colonization and contribute to NEC development [29] [30]. NEC is associated with lymphocyte imbalance within the intestinal mucosa, as TLR4 signalling in the intestinal epithelium leads to an upregulation of proinflammatory T helper 17 cells and a reduction in protective T regulatory cells [30].…”
Section: Hyper-reactive State Of Premature Intestinementioning
confidence: 99%
“…Furthermore, T lymphocytes have been shown to participate in the adaptation of the premature intestinal mucosa to bacterial colonization and contribute to NEC development [29] [30]. NEC is associated with lymphocyte imbalance within the intestinal mucosa, as TLR4 signalling in the intestinal epithelium leads to an upregulation of proinflammatory T helper 17 cells and a reduction in protective T regulatory cells [30]. Specifically, various investigators have identified roles for the increased expression and function of platelet-activating factor in the mucosal injury and barrier dysfunction associated with NEC [28] [31] [32].…”
Section: Hyper-reactive State Of Premature Intestinementioning
confidence: 99%